Co-existence of type 1 diabetes and other autoimmune ailments in subjects with autoimmune thyroid disorders. Issue 2 (February 2022) - Sharma, Himanshu; Sahlot, Rahul; Purwar, Naincy; Garg, Umesh; Saran, Sanjay; Sharma, Balram; Mathur, Sandeep K.
Abstract: Background and aims: Autoimmune thyroid dysfunction (AITD) is a significant autoimmune disorder affecting the population across age groups. The clustering of autoimmune diseases tends to occur within the same patients and families. Thus, this study aimed to determine the association of Type 1 diabetes and other autoimmune ailments in patients with autoimmune thyroid disorders. Methods: We performed a cross-sectional study, evaluating 500 subjects with a diagnosis of AITD (130 with Graves' disease; 370 with Hashimoto's thyroiditis) on presentation to our tertiary care centre to ascertain the prevalence of associated autoimmune disorders. Results: The frequency of Type 1 diabetes and other autoimmune disorders was 18.5% in Graves' disease and 27.8% in Hashimoto's thyroiditis patients. Coeliac disease (8.8%) (found in 6.9% of Graves' disease and 9.5% of Hashimoto's thyroiditis patients) and type 1 diabetes (7.8%) (found in 3.1% of Graves' disease and 9.5% of Hashimoto's thyroiditis patients) were the most common coexisting autoimmune disorders. Rheumatoid arthritis was the most common non-endocrine autoimmunity (2.8%). Female sex and duration of AITD more than five years were associated with increased odds of associated autoimmune disorders. Conclusion: A high prevalence of associated autoimmune disorders was observed in subjects with autoimmune thyroid dysfunction. We suggest the patients who remain symptomatic and those who develop other symptoms even with appropriate treatment undergo screening for associated autoimmune disorders, thus preventing a delay in diagnosis. Highlights: The associations between autoimmune thyroid diseases and other autoimmune disorders are well known but the data is sparse. Our study demonstrates a significant high prevalence of associated autoimmune disorders (25.4%). Coeliac disease, type 1 diabetes were most common followed by Addison's disease and rheumatoid arthritis. Female sex and longer duration of illness were associated with increased prevalence of other autoimmune disorders.